2016
DOI: 10.1093/nar/gkw1162
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel K311 ubiquitination site critical for androgen receptor transcriptional activity

Abstract: The androgen receptor (AR) is the main driver of prostate cancer (PC) development and progression, and the primary therapeutic target in PC. To date, two functional ubiquitination sites have been identified on AR, both located in its C-terminal ligand binding domain (LBD). Recent reports highlight the emergence of AR splice variants lacking the LBD that can arise during disease progression and contribute to castrate resistance. Here, we report a novel N-terminal ubiquitination site at lysine 311. Ubiquitinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Several studies have reported that AR levels are regulated by the ubiquitin-proteasome degradation pathway (24)(25)(26)(27). Several ubiquitin E3 ligases have also been implicated in AR-V7 degradation (28,29).…”
Section: Kif4a Stabilizes the Ar And Ar-v7 Proteins Via Competitive Imentioning
confidence: 99%
“…Several studies have reported that AR levels are regulated by the ubiquitin-proteasome degradation pathway (24)(25)(26)(27). Several ubiquitin E3 ligases have also been implicated in AR-V7 degradation (28,29).…”
Section: Kif4a Stabilizes the Ar And Ar-v7 Proteins Via Competitive Imentioning
confidence: 99%
“…Three AR ubiquitination sites have been reported. K845 and K847 are in the AR C-terminal region (AF-2) [ 8 ], whereas K311 is in the AR N-terminal region (AF-1) [ 9 ]. K845 and K847 sites are ubiquitinated by several E3 ligases such as RNF6, Siah2, SKP2, CHIP and MDM2 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitination of the K845 and K847 by SKP2, CHIP and MDM2 induce ubiquitin-mediated AR protein degradation, while RNF6 and Siah2-mediated ubiquitination of the K845 and K857 enhance AR transcriptional activity [ 8 ]. The K311 site was recently reported to be ubiquitinated by SKP2 [ 9 ]. Ubiquitination of the K311 is critical for both AR protein stability and AR transcriptional activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclei were washed in 1 ml of buffer A without glycerol and resuspended in 1ml of buffer B (3 mM EDTA, 0.2 mM EGTA, 1 mM DTT and 1 x protease inhibitor cocktail) on ice for 30 min. Finally, sample was centrifuged at 1500 g for 5 min at 4°C and the chromatin pellet was washed in buffer B seven times (43). (7).…”
Section: Methodsmentioning
confidence: 99%